Brazil - Innovation Increases Land Access and Incomes of Poor Rural Families - Roumani, Anna; Coirolo, Luis (World Bank, Washington, DC, 2012)
Brazil has developed a community-led, market-based approach to land reform in which poor rural laborers and farmers, either landless or with insufficient land for subsistence, form beneficiary associations through which to obtain financing to buy agricultural properties, for which they negotiate directly with willing sellers. The financing package includes complementary funds for investments to enhance land productivity (water, electricity, livestock, farm machinery) or improve welfare (housing, schools). The results are good: beneficiary incomes have increased substantially, predominantly from agricultural production, and the approach has accelerated the pace and lowered the cost of land access by the rural poor throughout the Northeast and elsewhere in Brazil.